PEREKAT UNTUK PEMBUATAN PELET PUPUK ORGANIK DARI RESIDU PROSES DIGESTASI ANAEROBIK LUMPUR BIOLOGI INDUSTRI KERTAS - Wardana, Krisna Adhitya; Soetopo, Rina S.; ., Saepulloh; Asthary, Prima Besty; Aini, Mukharomah Nur (Center for Pulp and Paper, 2015)
The residue from anaerobic digestion of paper mill biological sludge has the potency to be used as organic fertilizer. Physically, organic fertilizer in pellet form has smaller volume and easily stored and transported. The aim of this study is to obtain the appropriate adhesive to make fertilizer pellets from the residue from anaerobic digestion of paper mill biological sludge. The experiment were performed with two variable treatments which are the types of adhesive (sago flour, cassava starch, molasses) and the adhesive doses (0.5%, 1.0%, and 1.5%) with respectively 3 replications. The physical properties of resulting pellets were tested including yield, density, water holding capacity, and durability. The effect of pellets on plant germination and growth was also done using tomato seed. The results explained that generally, the pellets meet minimum requirements of organic fertilizers and soil conditioner according to Indonesian National Standard (SNI 7847:2012) unless Zn as micro nutrient and Regulation of the Minister of Agriculture Number 70/2011 unless water content. The pelletization of organic fertilizer to the size of 3-5 mm can be done by adding the best adhesive material, namely cassava starch 1% with the physical properties of the pellets including a yield of 99.56%, density of 1.84 g/mL, water holding capacity of 65.53%, and durability of 99.65-99.84%, but organic fertilizer pellets (with sago flour as adhesive) at a dose of 0.5 g/50 g media is the best for tomato germination and growth.Keywords: anaerobic digestion residue, organic fertilizer pellet, molasses, cassava starch, sago flourABSTRAKResidu proses digestasi anaerobik lumpur biologi industri kertas berpotensi dimanfaatkan sebagai pupuk organik. Secara fisik, pupuk organik dalam bentuk pelet lebih kecil volumenya dan lebih mudah disimpan dan diangkut. Tujuan penelitian ini adalah untuk memperoleh bahan perekat yang sesuai untuk membuat pelet pupuk organik dari residu proses digestasi anaerobik lumpur biologi industri kertas. Percobaan dilakukan dengan 2 variabel perlakuan, yaitu jenis perekat (tepung sagu, tepung kanji, molase) dan dosis perekat (0,5%; 1,0%; dan 1,5%) dengan masing-masing 3 replikasi. Pelet yang dihasilkan diuji sifat fisiknya meliputi yield, densitas, water holding capacity dan durabilitas. Percobaan pengaruh pelet berperekat terhadap perkecambahan dan pertumbuhan biji tanaman tomat juga dilakukan. Hasil penelitian menjelaskan bahwa secara umum, pelet memenuhi persyaratan minimal pupuk organik dan pembenah tanah sesuai SNI 7847:2012 kecuali Zn sebagai unsur hara mikro dan PERMENTAN No. 70 tahun 2011 kecuali kadar air. Pembuatan pelet pupuk organik dengan ukuran 3–5 mm dapat dilakukan dengan menambahkan bahan perekat terbaik, yaitu tepung kanji 1% dengan sifat fisik : yield 99,56%, densitas 1,84 g/mL, water holding capacity 65,53% dan durabilitas 99,65-99,84%, namun penggunaan pelet pupuk organik (berperekat tepung sagu) 0,5 g/50 g media untuk perkecambahan dan pertumbuhan biji tanaman tomat merupakan yang terbaik.Kata kunci: residu digestasi anaerobik, pelet pupuk organik, molase, tepung kanji, tepung sagu